Posyandu Cader Capacity Building: Prevent Stunting With Repair Nutrition 1000 HPK - Nita Dwi Astikasari,; Candra Wahyuni, (Journal of Health Science Community, 2023)
Government Indonesia initiated "Movement 1000 Day First Life (HPK)” For lower prevalence stunting, as well as problem not enough nutrition other. However, it turns out that the general public and Posyandu cadres are still not understand stunting, the 1000 HPK Movement, and stunting screening. Program This community service was carried out in July-August 2018 with method community relations. Participant program is cadre Integrated Healthcare Center in Village Ngara-arap, Ngaringan District, Grobogan Regency totaling 25 people (22 people follow the program to the end). The program includes advocacy activities and self-management, education of posyandu cadres regarding stunting, education of posyandu cadres about 1000 HPK in prevention stunting, training measurement Long Body (PB) and Height (TB) toddlers, and evaluation monitoring. Result of the program includes: 1) 88% of the target is to follow the program to the end, 2) Yes enhancement knowledge cadre about stunting And nutrition 1000 HPK after follow program Which be measured with questionnaire pre-post test (There is enhancement mark the average pre-test and post-test was 0.7 points), 3) 60% of the cadres were present able to practice how to measure body length (PB) and height (TB) toddlers are measured by observation, and 4) 40% of posyandu cadres are willing make transfers knowledge to society around through Integrated Healthcare Center.